2021
DOI: 10.3390/w13091276
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Spatial Shift in Flood Regime of the Kabul River Basin in Pakistan, Causes, Challenges, and Opportunities

Abstract: Recent evidence of regional climate change impacts on hydrological cycle directed us to study the floods in a high elevated and rapidly urbanized river basin, the Kabul River basin (KRB), Pakistan, which is susceptible to frequent flooding. Therefore, we analyzed the changes in flood regime at various spatial and temporal scales and their possible causes, which is accomplished by using flood indicators, trend analysis, change point analysis, and hydrological modeling. The results showed that the northern and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The Kabul River begins at the Unai pass base from the Hindu Kush mountains in Afghanistan, flowing toward the east and spanning 700 km to drain into the Indus River of Pakistan (Mehmood et al 2021).…”
Section: Description Of Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The Kabul River begins at the Unai pass base from the Hindu Kush mountains in Afghanistan, flowing toward the east and spanning 700 km to drain into the Indus River of Pakistan (Mehmood et al 2021).…”
Section: Description Of Datamentioning
confidence: 99%
“…Thus, it is essential to carefully manage and plan water resources to reduce loss of life and property damage caused by drought, floods, or heat waves (Ali, Shahbaz 2020; Mangukiya et al 2022). Climate changes influence the hydrological cycle globally; the resulting variations in weather and climate have increased the risks of drought and floods because weather changes, variations in precipitation, peak flows, and extreme temperatures have impacts on river discharge (Mehmood et al 2021). The amount of discharge generated from a catchment depends on various factors such as duration, meteorological variables, velocity, and water level (Gleason et al 2014;Saidi et al 2018;Malik et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have considered the VAR model with different orders for multivariate time series models and ARIMA models for univariate time series models [11][12][13]. Multivariate time series analysis (MVTSA) introduces a way to observe the relationship of a group of variables over time [14], thus making use of all possible information such as correlation [15].…”
Section: Related Workmentioning
confidence: 99%
“…To reduce the risk and effects of flooding, it is necessary to identify the flood-prone areas in current and predicted environmental conditions [4][5][6][7][8]. Recent studies related to climate change identified changes of flow regime, trend, and frequency of flood as well as investigated their causes through hydrological modeling for various spatio-temporal scales [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%